A meta-analysis of intercropping in Africa: impacts on crop yield, farmer income, and integrated pest management effects. Issue 1 (2nd January 2017) - Himmelstein, J.; Ares, A.; Gallagher, D.; Myers, J.
ABSTRACT: Poverty and hunger in Africa are prevalent and will increase in absolute terms with population growth and continued land degradation. Therefore, there is a need for sustainable agricultural strategies, such as conservation agriculture (CA) and integrated pest management (IPM). Among CA practices, intercropping holds the promise of providing benefits to smallholders through increased crop yields and income as well as improved resource use. We review intercropping's effects on crop yield, income, and output of IPM practices in Africa. On average, intercropping increases crop yields by 23% and gross income by 172 USD/ha, but effects vary significantly depending on management practices and agro-ecological factors. There was no evidence that yields and gross income for intercropping treatments increase when leguminous intercropping combinations, minimum/reduced tillage, pesticides, or fertilizers were utilized. Dual use of herbicides and intercropping practices garnered 1442 USD/ha more in gross income and yielded 1422 kg/ha more compared to those in conventionally managed fields, signifying the positive influence supplemental inputs can have on intercropping's effects. Although IPM practices increased yields by 20%, on average, IPM systems integrated with intercropping yielded 24% less than IPM systems that did not. This meta-analysis indicates that intercropping is an advantageous sustainable agricultural practice, but that its effective implementation would depend on considering other factors such as adequate control of competing vegetation. There is a clear need for more scientific studies which examine intercropping's role in complex sustainable agricultural systems, in order to understand its effects in differential environmental and socioeconomic situations and to optimize the practice's transfer and benefits.